Overcoming Scientific Cruelty: Bernard Rollin's Fight for Animal Rights. - Kipperman, Barry (American Journal of Economics & Sociology, 2025)
This essay focuses on the contributions of Dr. Bernard Rollin to the ethical treatment of animals. Rollin was a visionary who questioned systemic societal treatment of animals and promoted a new social ethic for animals. This new ethic centered on ensuring that animals have a "life worth living". Rollin taught the first class on veterinary ethics in the United States and considered the need to recognize and address animal pain as a moral imperative at a time when the subjective experience of animals was largely dismissed. Rollin did not believe that humans were inherently morally superior to non‐human animals. Rollin proposed that all sentient animals should have rights that protect them from oppression of fundamental aspects of their nature for the good of society. Rollin fought for improved treatment of animals in laboratories and on farms, via both the court of public opinion as well as legislation. Rollin understood that animal welfare is an increasing concern for society and that society looks to veterinary medicine for answers. He urged the veterinary profession to lead on ethical and animal welfare issues. Rollin recognized that what many referred to as "animal problems" were often problems created by, and solved by, humans and that humans were often secondary victims of moral stress when work‐related expectations or requirements discourage behaviors that could prevent animal suffering. Perhaps most importantly in our polarized socio‐political environment, Rollin strongly believed that achieving ethical change occurs when we can find common ground with those we disagree with.